2010
DOI: 10.1037/a0017780
|View full text |Cite
|
Sign up to set email alerts
|

Distorted symptom perception in patients with medically unexplained symptoms.

Abstract: The present study investigated differences in symptom perception between a clinical sample with medically unexplained symptoms (MUS) and a matched healthy control group. Participants (N = 58, 29 patients) were told that they would inhale different gas mixtures that might induce symptoms. Next, they went through 2 subsequent rebreathing trials consisting of a baseline (60 s room air breathing), a rebreathing phase (150 s, which gradually increased ventilation, PCO2 in the blood, and perceived dyspnea), and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 42 publications
6
69
2
3
Order By: Relevance
“…'false alarms'), seemingly contradicting the prediction of improved accuracy. Similarly, Van den Bergh and colleagues found significantly lower correspondence between induced respiratory changes and self-reported breathlessness in a CO 2 inhalation paradigm for non-clinical MUS reporters (Bogaerts et al, 2008) and MUS patients (Bogaerts et al, 2010b).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 90%
See 1 more Smart Citation
“…'false alarms'), seemingly contradicting the prediction of improved accuracy. Similarly, Van den Bergh and colleagues found significantly lower correspondence between induced respiratory changes and self-reported breathlessness in a CO 2 inhalation paradigm for non-clinical MUS reporters (Bogaerts et al, 2008) and MUS patients (Bogaerts et al, 2010b).…”
Section: Interoceptive Hypervigilance Thresholds and Awarenessmentioning
confidence: 90%
“…This effect only appeared when participants were asked to rate "symptoms" (e.g., dyspnea/breathlessness) and not when rating neutrally labelled "sensations" (e.g., breathing intensity), showing that a reduction in sensory-perceptual detail is only applied when contextual cues advance symptom-related priors (Bogaerts et al, 2005(Bogaerts et al, , 2008(Bogaerts et al, , 2010b. Less detailed sensoryperceptual processing of somatic episodes in SSD patients may also underlie the absence of a peak-end bias when evaluating previous somatic episodes (Bogaerts et al, 2012) and less specific healthrelated autobiographical memories (Walentynowicz et al, 2016).…”
Section: Threat and Negative Affect (Na)mentioning
confidence: 97%
“…A symptom is any subjective sensation or perceived change in bodily function which only the individual can perceive. Research has shown that symptoms are influenced by cognitive processes [Bogaerts et al 2010]. In this evaluation there was heightened awareness by building occupants of a suspected problem in the building.…”
Section: Discussion Employee Interviewsmentioning
confidence: 74%
“…These symptoms are rarely caused by serious illness. In fact, 15%-50% of primary care visits are for what is termed "medically unexplained symptoms" [Kirmayer et al 2004;Jackson et al 2009;Bogaerts et al 2010].…”
Section: Discussion Employee Interviewsmentioning
confidence: 99%
“…We have learned from prior indoor environmental evaluations that often symptoms reported by building occupants are wide ranging, do not suggest a particular medical diagnosis, and are not readily associated with a causative agent. Symptoms are influenced by cognitive (thought) processes [Bogaerts et al 2010] and are more common when pollution or health threats are perceived, as on the seventh floor [Watson and Pennebaker 1989;Williams and Lees-Haley 1993]. Of the general population, 86%-95% have one or more common symptoms during any 2-to 4-week period.…”
Section: Employee Healthmentioning
confidence: 99%